Why setbacks are compatible with progress in assimilating problematic themes: Illustrations from the case of Alicia. (3rd April 2021) - Caro Gabalda, Isabel; Stiles, William B.
Abstract: Objective : This theory-building case study investigated setbacks in assimilation, seeking to replicate and elaborate previous work, in which most setbacks were one of two types, balance strategy (BS) or exceeding the therapeutic zone of proximal development (TZPD). Method : We studied the case of Alicia, a 26 year-old woman, treated successfully for depression. Her main problematic experiences were rated with the Assimilation of Problematic Experiences Scale (APES), and 267 setbacks were identified. We classified the setbacks and examined them quantitatively and qualitatively. Results : Alicia showed the usual irregular progress of assimilation, with generally increasing APES ratings, consistent with the improvements in outcome measures. Almost all setbacks could be distinguished as BS or TZPD. Replicating a previously observed pattern, BS setback passages tended to be at or above APES stage 3, whereas TZPD setback passages tended to be below APES stage 3. BS and TZPD setbacks also drew qualitatively different characterizations. Conclusion : Results represented a conceptual replication of previous work, explainable using the same theoretical tenets. As an integral part of therapeutic work, setbacks do not impede progress in therapy. BS and TZPD setbacks reflect different processes and have different implications for how therapist and client are working together.